Political Implications of AI in Governance - Ade Fitria Fatimah (Politeknik Siber Cerdika Internasional, 2024)
The advent of artificial intelligence (AI) is rapidly transforming governance, policy-making, and political decision-making, introducing unprecedented opportunities and challenges for public administration. This study explores the multifaceted implications of AI adoption within government institutions, focusing on its influence on policy formulation, administrative efficiency, and decision-making processes. By analyzing case studies and recent advancements in AI-driven governance frameworks, the research evaluates how AI tools are being employed to streamline public services, improve policy accuracy, and increase governmental transparency. Additionally, the study investigates ethical and privacy concerns, highlighting the risks of bias, the erosion of accountability, and the potential for reduced human oversight in critical decision-making areas. Through a comparative analysis of various governance models, this paper underscores the dual nature of AI in governance: while AI has the potential to optimize administrative functions and foster data-driven policies, it also poses complex ethical questions that demand careful consideration. The findings provide a roadmap for policymakers, suggesting best practices for balancing technological benefits with democratic accountability, ultimately guiding the responsible integration of AI into governance. This study contributes to the discourse on AI’s role in reshaping the future of governance and offers insights into the sustainable adoption of AI in public administration.